Peran Orang Tua dalam Menerapkan Pembelajaran Penjas di Rumah saat Pandemi Covid-19 (Indonesian Journal for Physical Education and Sport, 2022)
The Covid-19 pandemic has disrupted all activities, one of which is the learning process at school. Researchers took the initiative to analyze the role of parents in implementing physical education learning at home during a pandemic. The purpose of this study is to find out and identify how parents provide guidance to children when learning physical education online at home. Sources of data obtained from interviews and questionnaires to parents of elementary school students in Gondoriyo Village. The type of research is survey or field research with the research approach used is descriptive qualitative approach. Sampling of data sources was carried out sample purposive. Data collection techniques by means of interviews and observations. The results of this study are the learning process is very disturbed and the role of parents for students is very influential, because for students who are still in elementary school, of course they still do not fully understand what is happening at this time so they only follow orders and input from other people. old because all learning is only done remotely. Most parents always guide their children during the online physical education learning process. Based on the results of this study, the researcher gives advice to parents should pay more attention to their children's education by always providing encouragement to continue learning. Increase participation as much as possible to be able to guide and direct children in physical education learning. There is a need to improve the relationship between parents and their children.